Gedagtes oor die begin van die kerk - "n geskiedenis van versoenende verskeidenheid - Aarde, Andries van (Hervormde teologiese studies, 1987)
Thoughts on the beginnings of the church as a history of reconciliating diversity Against the backdrop of the beginnings of the church, the article makes a plea for modem believers to take the humanity of the church more seriously in their forming of ecclesiastical structures. The development of the concept 'church unity' in the New Testament was part of the attempt to establish firstly continuation in the Jesus-movement and secondly mutual fellowship among the conflicting Jewish and Hellenistic Christians during the very beginnings of the church in the first century. Thoughts on the beginnings of the church, therefore, should not be from the perspective of institutional unity but from reconciliating diversities. Modem ideas regarding the unity of the church originated from the late-twentieth century philosophy of holism and shouldn't be anachronistically seen as the concretisation of a Biblical idea.